Sistem Pembagian Waris Sama Rata Pada Masyarakat Watukumpul Kabupaten Pemalang - Sarah Hedianti, Elfira (Al-Hukkam: Journal of Islamic Family Law, 2022)
Inheritance law has been regulated in Islam clearly, but in reality in society it is still notwell socialized. This is inseparable from the influence of Indonesia, whose population hasvarious forms of culture that include knowledge, beliefs, arts, morals, and customs. From this cultural diversity, society does not only have one form of law, but many forms of law that develop and bind and change society. In this case, the author is interested in studying further, about how the practice of inheritance distribution patterns in the Watukumpul community, Pemalang Regency, and what factors influence the Watukumpul community in Pemalang Regency using this pattern. This study aims to explain the legal culture of the Watukumpul community, Pemalang Regency regarding the pattern of inheritance distribution and the factors that influence it. The results of this study are expected to be useful as a reference for readers, and readers are expected to better understand the pattern of inheritance distribution and can provide alternative solutions to the problems faced. This research was conducted in Watukumpul District, Pemalang Regency. This type of research is field research. Using primary data sources in the form of interviews with the Watukumpul community. Meanwhile, secondary data sources were obtained from books, journals, and other documents related to research problems. Then the data was analyzed using a qualitative analysis approach. The results of this study indicate that: first, the pattern of inheritance distribution carried out by the people of Watukumpul, Pemalang Regency in general there are 2 (two) patterns, namely inheritance before the heir dies and inheritance after the heir dies. Although the majority of the population is Muslim, most of the inheritance process that runs is when the heir is still alive. This is done with various considerations, such as because it has become a custom, preventing disputes between heirs, as capital for life if the child is married. Second, in general, the people of Watukumpul, Pemalang Regency, use the pattern of inheritance distribution because they follow and undergo conditions that already apply in their environmental order.